Laudatio a Diego Valadés - Dalla Vía, Alberto Ricardo (2015)
Speech given at the Faculty of Law by "... the Director of the Department of Public Law I, representing the professors of Constitutional Law and Theory of State and at the initiative of Professor Dr. Raúl Gustavo Ferreyra, ... we come to request the "Honoris Causa" doctorate from the University of Buenos Aires to the distinguished mexican jurist Diego Valadés, born in Mazatlán, Sinaloa, in 1945"